Coral community shifts across major reef crises - Dimitrijevic, Danijela; Raja Schoob, Nussaibah Begum; Kießling, Wolfgang (ICRS 2021, 14th International Coral Reef Symposium, 2021)
Coral communities today are negatively affected by anthropogenic greenhouse gas release causing global warming and ocean acidification. Natural greenhouse gas release by massive volcanism is thought to have caused one of the Big Five mass extinctions at the end of the Triassic period (200 million years ago). This hyperthermal event triggered one of the greatest reef crises and the most substantial evolutionary crisis in the history of scleractinian corals. While the diversity dynamics of corals are well studied, research on changes in community composition at this time is still lacking. We provide a quantitative assessment of community changes at the level of morphological traits (ie corallite sizes, growth form, and colony form). Using our new Reef Traits Database (RTD), we show that corallite sizes of colonial corals increased substantially after the end-Triassic reef crisis. We conclude that a change towards increasing heterotrophy in reef coral communities best explains the observations across the end-Triassic reef crisis. Additionally, we test how much of the trend in corallite size is governed by selective extinction, origination, and changes in relative abundance across coral communities. Therefore, the fossil record showcases the balance of evolutionary adaptation versus extinction and the lasting community changes in response to climate change over longer time frames than we could cover by studying the extant coral communities. We conclude that a change towards increasing heterotrophy in reef coral communities best explains the observations across the end-Triassic reef crisis. Additionally, we test how much of the trend in corallite size is governed by selective extinction, origination, and changes in relative abundance across coral communities. Therefore, the fossil record showcases the balance of evolutionary adaptation versus extinction and the lasting community changes in response to climate change over longer time frames than we could cover by studying the extant coral communities. We conclude that a change towards increasing heterotrophy in reef coral communities best explains the observations across the end-Triassic reef crisis. Additionally, we test how much of the trend in corallite size is governed by selective extinction, origination, and changes in relative abundance across coral communities. Therefore, the fossil record showcases the balance of evolutionary adaptation versus extinction and the lasting community changes in response to climate change over longer time frames than we could cover by studying the extant coral communities.<br